2023
DOI: 10.1055/s-0043-1764482
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidia in HIV-Positive and HIV-Negative Pediatric Patients with Diarrhea at a Tertiary Care Hospital

Abstract: Background Human microsporidiosis presents as an important and rapidly emerging opportunistic infection. However, the exact burden of this infection especially in the pediatric population of Northern India remains unknown. In this study, we investigated the prevalence of microsporidia among human immunodeficiency virus (HIV)-positive and HIV-negative pediatric patients who presented with diarrhea. Methods A total of 263 children were recruited consisting of 98 HIV seropositive with diarrhea and 165 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Besides, there is no new pathognomonic change in head MR, and the patient also had no complaints of ocular discomfort. Dinesh ( 11 ) reported that microsporidia are one of the main causes of intestinal infection in HIV-positive children. HIV-infected children usually have low immune function, while this patient’s early T-cell subset and B-cell subset decreased significantly after transplantation, indicating slow immune reconstitution and susceptibility to various pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there is no new pathognomonic change in head MR, and the patient also had no complaints of ocular discomfort. Dinesh ( 11 ) reported that microsporidia are one of the main causes of intestinal infection in HIV-positive children. HIV-infected children usually have low immune function, while this patient’s early T-cell subset and B-cell subset decreased significantly after transplantation, indicating slow immune reconstitution and susceptibility to various pathogens.…”
Section: Discussionmentioning
confidence: 99%